Allergen‐induced interleukin‐18 promotes experimental eosinophilic oesophagitis in mice. Issue 10 (24th March 2015) - Dutt, Parmesh; Shukla, Jai Shankar; Ventateshaiah, Sathisha Upparahalli; Mariswamy, Siddesha Jalahalli; Mattner, Jochen; Shukla, Anshi; Mishra, Anil
Abstract : Elevated levels of interleukin (IL)‐18 have been reported in a number of allergic diseases. We recently reported that IL‐18 in the blood and IL‐18Rα mRNA in the oesophagus are induced during human eosinophilic oesophagitis (EoE). Additionally, we earlier showed that invariant natural killer T (iNKT) cells are critical to EoE pathogenesis; however, the mechanism of iNKT cell activation in EoE is not well understood. Therefore, the current study focused on the hypothesis that allergen‐induced IL‐18 may have an important role in iNKT cell‐mediated EoE pathogenesis. We first validated the human EoE findings of IL‐18 in experimental EoE by examining blood levels of IL‐18 and oesophageal IL‐18Rα mRNA levels in aeroallergen‐ and food allergen‐induced experimental mouse models of EoE. We demonstrate that blood IL‐18 protein and oesophageal IL‐18Rα mRNA are induced in the mouse model of EoE and that IL‐18Rα is expressed by iNKT cells in the oesophagus. Intranasal delivery of rIL‐18 induced both mast cells and eosinophilic inflammation in the oesophagus in a time‐ and dose‐dependent manner. To establish the significance of IL‐18 in EoE pathogenesis, we examined DOX‐inducible rtTA‐CC10‐IL‐18 bitransgenic mice that induce IL‐18 protein expression in the oesophagus. Our analysis indicated that induction of IL‐18 in these mice resulted in the development of many of the characteristics of EoE, including oesophageal intraepithelial eosinophilia, increased mast cells, oesophageal remodelling and fibrosis. The current study provides evidence that IL‐18 may induce iNKT cell activation to release the eosinophil‐activating cytokine IL‐5, as IL‐5‐deficient mice and iNKT cell‐deficient (CD1d null) mice do not induce EoE in response to intranasal IL‐18 challenge. Taken together, these findings provide evidence that allergen‐induced IL‐18 has a significant role in promoting IL‐5‐ and iNKT‐dependent EoE pathogenesis.